Gemcitabine Switch Maintenance Superior to Supportive Care in Advanced NSCLC - Coltrera, Francesca (MD Conference Express, 2015)
This prospective randomized open-label trial compared gemcitabine maintenance switch therapy with best supportive care following platinum doublet chemotherapy in patients with stage IIIB and IV non–small cell lung cancer. This small trial found gemcitabine switch maintenance to be associated with a longer median overall and progression-free survival, although with a higher incidence of high-grade adverse events. Its results will need to be analyzed more carefully when information about the frequency of follow-up and the rates of subsequent systemic therapy is available.